CATCHING ADULT OF Premnotrypes vorax (HUSTACHE) WITH ADULT OF THE SAME SPECIES AS ATTRACTANT - CALVACHE-G., HUGO (Revista Colombiana de Entomología, 1985)
In the present study, realized at the ICA's Experimental Center "Obonuco" (Pasto - Nariño), the attraction of alive adults, males and females, of the Andean Weevil, Premnotrypes vorax (Hustache) was evaluated, using virgin individuals obtained in the insectary and field-collected adults possibly after copulation. Pitfall traps for Coleoptera were used, placing on the underside of the protective cover micro cage with the alive insects. The effect of potato plant juice was also tested; as a check, traps without any attractants were used. The traps were randomly distributed in a potato stubble, where potatoes were planted again. The observations were realized from before soil preparation to harvest. The total capture of adults summed up 4435, corresponding the mayor volume to the period covered from soil preparation to a week after germination; then the capture of insects declined. Both males and females showed the same range of attraction, which is attributed to an aggregation pheromone and is not of the sexual type. No differences were found between the number of individuals used, which varied from 3 to 12. The capture obtained with the potato juice was very low and similar to that of the check.